Semantic Analysis of Passive Sentence Translation in Novel The Hunger Games: Mockingjay By Suzanne Collins - Oktariani, Lionora; Boeriswati, Endry; Ekowati, Sri Harini (citeus, 2018)
This study aims at analyzing the translation of English passive sentences into Indonesian language, in terms of the meanings and equivalence which appear in the translation. The method used to analyze the data is a descriptive quantitative. The sample of this research is taken from five chapters of the novel Hunger Games: Mockingjay by Suzanne Collins. The result shows that the translation of passive sentences comes into several types of meanings: lexical meaning 37%, grammatical meaning 2%, textual meaning 5%, and contextual meaning 46%. The translation of passive sentences also falls into two types of equivalences: formal equivalence 35% and dynamic equivalence 60%. However, 5% belongs to no equivalent translation. In conclusion, the English passive sentences are mostly translated contextually so that the type of equivalence mostly appeared is dynamic equivalence. Hence, inventive ability, creativity, and experience are required to grasp the exact meaning of source text.